Pengaruh Metode Pemberian Tugas (Take Home) Terhadap Minat Belajar Anak Kelompok B Di Tk Dharma Wanita Gedangan Mojokerto - Indri Dwi Isnaini (JCE (Journal of Childhood Education), 2018)
One of the external factors that affect the child's interest in learning is the assignment of homework or homework. According to Muijs, et al (2008: 150) "Homework can be defined as an out-of-class activity that is an extension of classroom work". The purpose of this study to determine the effect of methods of assignment to the interests of learning children. To answer the above problems, researchers conducted a quantitative descriptive study. This research was conducted in Group B TK Dharmawanita Gedangan Mojokerto academic year 2016/2017. Subjects in the study amounted to 20 children. Technique of data collection is done through observation, interview and documentation. Observations before the recapitulation treatment were obtained on average, ie 0% of children in the Very High (ST) category, 3.33% of children in the High (T) category, 13.33% of children in Medium (S) category, and 83.33% of children in the Low category (R), on the observation aspect of child's interest, Child's attention in learning and child involvement. Observations after treatment were obtained an average of 35.28% of children belonging to the category Very High (ST), Next to the category High (T) obtained an average of 17.61%. In the Medium category (S), the mean is 20.28%, and for the Low category (R), the average is 26.83%, the observation aspect of the child's interest, the child's attention in learning and the involvement of the child